Exercises in plant physiology - Witham, Francis H. (Prindle, Weber & Schmidt, 1986)
Exercises intended for use in a one or two term course in introductory plant physiology. Exercises vary in content and complexity and present a broad spectrum of basic physiological concepts and techniques.